2016
DOI: 10.15376/biores.11.4.8470-8482
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Rice Husk-Incorporated Recycled Thermoplastic Blend Composites

Abstract: High-fiber-content composites made from rice husk (RH) (from 50 up to 80 wt%) as well as a recycled thermoplastic blend (rTPB) were fabricated using a two-step extrusion and hot/cold press molding technique. The temperature dependency of the thermal degradation and dynamicmechanical behavior was investigated using thermogravimetric analysis (TGA) and dynamic mechanical analysis (DMA). The long-term water absorption and orthotropic swelling were analyzed following immersion in distilled, tap, and sea water for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 22 publications
2
24
0
1
Order By: Relevance
“…Vinylester/carbon specimens showed 8.57% degradation whereas isopolyester/carbon specimen showed reduction in ILSS of 10.5% at 60 0 C for duration of 196 days at hygrothermic conditions. The similar observations at higher duration and temperature had higher moisture absorption as reported by Chen et.al [16][17]. All the composite specimen analysed showed degradation in UTS, flexural strength and ILSS due to hygrothermic condition.…”
Section: Durability Studies At Hygrothermic Conditionsupporting
confidence: 88%
“…Vinylester/carbon specimens showed 8.57% degradation whereas isopolyester/carbon specimen showed reduction in ILSS of 10.5% at 60 0 C for duration of 196 days at hygrothermic conditions. The similar observations at higher duration and temperature had higher moisture absorption as reported by Chen et.al [16][17]. All the composite specimen analysed showed degradation in UTS, flexural strength and ILSS due to hygrothermic condition.…”
Section: Durability Studies At Hygrothermic Conditionsupporting
confidence: 88%
“…Alemdar and Sain (2008) also reported that chemical treatment of wheat straw resulted in alteration of the surface structure and chemical composition of the fiber. The development of such changes on the surface structure of the fiber creates advantages for binding through mechanical interlocking between the fiber and polymer matrix in the composites (Chen et al 2016a). Conversely, raw fiber surface structure appeared devoid of surface indentations and covered with numerous impurities, as indicated in Fig.…”
Section: Scanning Electron Microscopymentioning
confidence: 99%
“…Alkaline treatment of natural fiber surfaces is the most widely used method to modify fiber surfaces and improve the interfacial interaction and adhesion between the fiber and polymer matrix. Chen et al (2016a) showed that alkaline treatment of natural fiber induces surface roughness and fibrillation that provide site of mechanical interlocking between fiber and matrix.…”
mentioning
confidence: 99%
“…It has also been proven that the addition of wood dust to recycled polyethylene terephthalate (PET) enhanced the mechanical properties of the PET polymer matrix composites (Rahman et al, 2016). It has also been proven that reinforcement of recycled high density polyethylene (HDPE) and PET polymer matrix by rice husk particles led to an improvement in the mechanical properties of the composites (Chen et al, 2016). The addition of cow bone particles to recycled low density polyethylene (LDPE) enhanced the mechanical properties of the LDPE polymer matrix composites (Agunsoye et al, 2013).…”
Section: Introductionmentioning
confidence: 99%